2021
DOI: 10.1007/s40266-021-00903-0
|View full text |Cite
|
Sign up to set email alerts
|

Renal Function, Cardiovascular Diseases, Appropriateness of Drug Prescription and Outcomes in Hospitalized Older Patients

Abstract: Introduction Reduced estimated creatinine clearance (eCrCl) is prevalent in older patients and impacts on drug prescription. In this study, the burden of eCrCl reduction and its associated factors and impact on outcomes were analyzed. Moreover, the rate of inappropriate drug prescription according to eCrCl and its impact on outcomes were described. Methods Data were obtained from "REgistro POliterapie SIMI" (REPOSI), a prospective observational register enrolling hospitalized patients aged ≥ 65 years. Patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…In general, older subjects tend to be at a higher risk of metabolic disorders and atherosclerotic diseases [20,21], and their renal function is vulnerable to several treatment interventions [22]. Therefore, such a risk of impaired renal function represents a barrier to the use of the most appropriate drug intervention.…”
Section: Discussionmentioning
confidence: 99%
“…In general, older subjects tend to be at a higher risk of metabolic disorders and atherosclerotic diseases [20,21], and their renal function is vulnerable to several treatment interventions [22]. Therefore, such a risk of impaired renal function represents a barrier to the use of the most appropriate drug intervention.…”
Section: Discussionmentioning
confidence: 99%
“…According to a retrospective study conducted at a university hospital in Stockholm, Sweden, adverse drug reactions accounted for 14% of admissions, while impaired renal function accounted for one-third [ 56 ]. An Italian study of older patients with renal impairment found that RIM use was independently associated with a 46% increase in mortality [ 27 ] and a 40% increase in mortality in a French population-based study [ 36 ]. RIMs, however, were not associated with hospitalization or death in one study of community-dwelling older adults [ 24 ].…”
Section: Reviewmentioning
confidence: 99%
“… 14 According to studies of older patients with renal impairment, use of RIM was associated with an increase in mortality of 40% to 46%. 11 , 15 Moreover, exposure to nephrotoxic medications increased healthcare utilization, including prescription drug use, emergency department visits, and hospitalizations. A study has demonstrated that total health expenditures were nearly 30% higher in groups exposed to nephrotoxic medications than in those who were not exposed.…”
Section: Introductionmentioning
confidence: 99%